ISOLASI DNA METAGENOMIK DARI TANAH HUTAN MANGROVE PANTAI SUWUNG BALI - Wirajana, I Nengah; Asih Yuliana, Darma; Ratnayani, Ketut (Jurnal Kimia (Journal of Chemistry), 2013)
Metagenomic DNA isolation from mangrove forest soils of Suwung Beach-Bali was conducted to exploit the biocatalytic potential of microbial communities for the discovery of novel cellulase. The whole DNA isolation was conducted by modification of preparation step by Marco (2010) and DNA extraction step by Amorim et al (2008). The results of metagenomic DNA isolation were analyzed by spectrophotometry and agarose gel electrophoresis. The results showed that whole DNA was able be isolated successfully, but protein and humic acid were found as contaminant.
Keywords: Cellulase, metagenomic DNA, mangrove forest soil